(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this paper we analyze an interesting Early Iron Age pottery fragment from El Cabezo del Lugar (Azaila, Teruel). Its surface shows an incised zoomorphic and geometric decoration, including a cervid-shaped pattern. At the same time, we describe the archeological context of the find- ing and we provide an exam of the closest iconographic parallels. Finally, suggest some hypothesis regarding the function and meaning of the object.